2023
DOI: 10.2152/jmi.70.208
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of corrective exercises on the KOJI AWARENESS score and activity-related pain intensity

Abstract: Background : The KOJI AWARENESS™ screening test is a self-administered screening tool for assessment of mobility, stability, and strength. It provides corrective exercises corresponding to the individual's answers to the KOJI AWARENESS™ test questions. However, there is no evidence of the effectiveness of corrective exercises in improving KOJI AWARENESS™ screening test scores and activity-related pain. Methods : Twenty-six healthy subjects (11 female and 15 male ; age 20-50 years) were selected for participati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The results of this study confirm that KOJI AWARENESS TM sub-component scoring is, to some extent, valid for assessing physical function. Various researchers have reported that a decline in musculoskeletal functions, such as flexibility, muscle strength, and balance, is a risk factor for physical pain and orthopedic disorders [4851]. If KOJI AWARENESS TM becomes commonplace and the practice of self-assessing and improving the scores of musculoskeletal and other physical functions becomes widespread, it can be expected to reduce the risk of developing pain and orthopedic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study confirm that KOJI AWARENESS TM sub-component scoring is, to some extent, valid for assessing physical function. Various researchers have reported that a decline in musculoskeletal functions, such as flexibility, muscle strength, and balance, is a risk factor for physical pain and orthopedic disorders [4851]. If KOJI AWARENESS TM becomes commonplace and the practice of self-assessing and improving the scores of musculoskeletal and other physical functions becomes widespread, it can be expected to reduce the risk of developing pain and orthopedic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…According to the data provided, individuals scoring below 22 on the MFMS should be prioritized due to their increased susceptibility to training injuries. Early identification of this group of people enables healthcare professionals to implement appropriate training interventions (corrective training) to reduce injury risks [ 22 ]. Additionally, clinicians and trainers can utilize the MFMS to monitor progress during rehabilitation, as enhancements in physical function are likely to be evident in MFMS evaluation outcomes.…”
Section: Discussionmentioning
confidence: 99%